Enter natural log statement


  

Evaluate the following logarithmic expression

logof200

Evaluate logof200

You didn't enter a base

We'll do bases e and 2-10

Evaluate loge(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = e and x = 200, we have:

loge(200)  =  Ln(200)
  Ln(e)

Ln(e) = 1

loge(200) = 5.298317366548

Evaluate log2(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 2 and x = 200, we have:

log2(200)  =  Ln(200)
  Ln(2)

log2(200) = 7.6438561897747

Evaluate log3(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 3 and x = 200, we have:

log3(200)  =  Ln(200)
  Ln(3)

log3(200) = 4.8227363021502

Evaluate log4(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 4 and x = 200, we have:

log4(200)  =  Ln(200)
  Ln(4)

log4(200) = 3.8219280948874

Evaluate log5(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 5 and x = 200, we have:

log5(200)  =  Ln(200)
  Ln(5)

log5(200) = 3.2920296742202

Evaluate log6(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 6 and x = 200, we have:

log6(200)  =  Ln(200)
  Ln(6)

log6(200) = 2.9570472251115

Evaluate log7(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 7 and x = 200, we have:

log7(200)  =  Ln(200)
  Ln(7)

log7(200) = 2.7227965120179

Evaluate log8(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 8 and x = 200, we have:

log8(200)  =  Ln(200)
  Ln(8)

log8(200) = 2.5479520632582

Evaluate log9(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 9 and x = 200, we have:

log9(200)  =  Ln(200)
  Ln(9)

log9(200) = 2.4113681510751

Evaluate log10(200) using the Change of Base Formula

The formula for the change of base rule in logb(x) is as follows:

logb(x)  =  Ln(x)
  Ln(b)

Given b = 10 and x = 200, we have:

log10(200)  =  Ln(200)
  Ln(10)

log10(200) = 2.301029995664

Final Answer

loge(200) = 5.298317366548
log2(200) = 7.6438561897747
log3(200) = 4.8227363021502
log4(200) = 3.8219280948874
log5(200) = 3.2920296742202
log6(200) = 2.9570472251115
log7(200) = 2.7227965120179
log8(200) = 2.5479520632582
log9(200) = 2.4113681510751
log10(200) = 2.301029995664





What is the Answer?
loge(200) = 5.298317366548
log2(200) = 7.6438561897747
log3(200) = 4.8227363021502
log4(200) = 3.8219280948874
log5(200) = 3.2920296742202
log6(200) = 2.9570472251115
log7(200) = 2.7227965120179
log8(200) = 2.5479520632582
log9(200) = 2.4113681510751
log10(200) = 2.301029995664
How does the Logarithms and Natural Logarithms and Eulers Constant (e) Calculator work?
Free Logarithms and Natural Logarithms and Eulers Constant (e) Calculator - This calculator does the following:
* Takes the Natural Log base e of a number x Ln(x) → logex
* Raises e to a power of y, ey
* Performs the change of base rule on logb(x)
* Solves equations in the form bcx = d where b, c, and d are constants and x is any variable a-z
* Solves equations in the form cedx=b where b, c, and d are constants, e is Eulers Constant = 2.71828182846, and x is any variable a-z
* Exponential form to logarithmic form for expressions such as 53 = 125 to logarithmic form
* Logarithmic form to exponential form for expressions such as Log5125 = 3

This calculator has 1 input.

What 8 formulas are used for the Logarithms and Natural Logarithms and Eulers Constant (e) Calculator?

Ln(a/b) = Ln(a) - Ln(b)
Ln(ab)= Ln(a) + Ln(b)
Ln(e) = 1
Ln(1) = 0
Ln(xy) = y * ln(x)




For more math formulas, check out our Formula Dossier

What 4 concepts are covered in the Logarithms and Natural Logarithms and Eulers Constant (e) Calculator?

euler
Famous mathematician who developed Euler's constant
logarithm
the exponent or power to which a base must be raised to yield a given number
natural logarithm
its logarithm to the base of the mathematical constant e
eLn(x) = x
power
how many times to use the number in a multiplication
Example calculations for the Logarithms and Natural Logarithms and Eulers Constant (e) Calculator
Logarithms and Natural Logarithms and Eulers Constant (e) Calculator Video

Tags:



Add This Calculator To Your Website